Psychological Resilience During Illness in Patients Recovered from Cancer - Gupta, Sachin; Li, Jinghua; Zhou, LuXin (KMAN Counseling & Psychology Nexus, 2024)
Cancer survivors face significant psychological challenges post-treatment, which necessitates an understanding of the resilience mechanisms they employ to cope and thrive. This study aims to explore the psychological resilience of cancer survivors, identifying the emotional responses, coping strategies, support systems, and personal growth experienced during and after their recovery. This qualitative study employed semi-structured interviews with 26 cancer survivors who had completed treatment at least six months prior. The sample included a diverse group of participants in terms of age, gender, and cancer type. Data collection aimed at theoretical saturation and analysis was conducted using NVivo software, following a grounded theory approach to identify themes and sub-themes within the narratives. Four main themes were identified: Emotional Responses, Coping Strategies, Support Systems, and Reflections and Growth. Each theme encompassed several categories with specific concepts: Emotional Responses included initial reactions, coping during treatment, and post-treatment emotions; Coping Strategies covered personal strategies, reliance on support systems, and spiritual and philosophical approaches; Support Systems highlighted the role of family and friends, healthcare providers, and community networks; Reflections and Growth focused on changes in self-perception, impact on relationships, and shifts in life philosophy. The study underscores the complexity of the resilience process among cancer survivors, revealing a broad spectrum of emotional responses, adaptive coping mechanisms, and the crucial role of support systems. The findings emphasize the need for holistic approaches in oncological care that address not only the physical but also the psychological and social aspects of cancer survivorship.